Wireless power transfer : between distance and efficiency - Zhong, Wenxing; Xu, Dehong; Hui, Ron Shu Yuen (Singapore : Springer Nature Singapore Pte. Ltd., 2020)
Focusing on inductive wireless power transfer (WPT), which relies on coil resonators and power converters, this book begins by providing the background and basic theories of WPT, which are essential for newcomers to the field. Then two major challenges of WPT - power transfer distance and efficiency - are subsequently addressed, and multi-resonator WPT systems, which not only offer a way to extend power transfer distance but also provide more flexibility, are investigated. Recent findings on techniques to maximize the power transfer efficiency of WPT systems, e.g. maximum efficiency point tracking, are also introduced. Without the constraint of cables, wireless power transfer (WPT) is an elegant technique for charging or powering a range of electrical devices, e.g. electric vehicles, mobile phones, artificial hearts, etc. Given its depth of coverage, the book can serve as a technical guideline or reference guide for engineers and researchers working on WPT.
Includes bibliographical references.
Keywords: Wireless power transmission